Vèmes Journées, Toulon 1998
DOI: 10.5150/jngcgc.1998.038-r
|View full text |Cite
|
Sign up to set email alerts
|

Pieux sous charges latérales : étude de l'effet de groupe

Abstract: RESUME: Afin d'étudier l'effet de groupe sur des pieux chargés latéralement, des essais sur modèles réduits de couples de pieux ont été réalisés avec la centrifugeuse du Laboratoire Central des Ponts et Chaussées. Une méthode a été établie pour obtenir les courbes de réaction P-y à partir des résultats expérimentaux. On compare ensuite ces courbes à des codes de calcul reconnus : Fascicule 62 (France), Port and Harbour Research Institute (Japon) et l'American Petroleum Institute (D.S.A). Les déplacements en tê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 4 publications
2
15
1
6
Order By: Relevance
“…This is clearly an outlier and it is concluded that the ratio between diameter of the pile and diameter of average grain size d/d 50 5 88 is too small, which leads to a grain size effect. This ratio is 30% higher than reported by Remaud (1999). The response is more or less identical until a normalised deflection of 0?1 is reached for the four other piles, and the loaddeflection curves start to deviate at larger deflections.…”
Section: Grain-size Effectcontrasting
confidence: 46%
See 4 more Smart Citations
“…This is clearly an outlier and it is concluded that the ratio between diameter of the pile and diameter of average grain size d/d 50 5 88 is too small, which leads to a grain size effect. This ratio is 30% higher than reported by Remaud (1999). The response is more or less identical until a normalised deflection of 0?1 is reached for the four other piles, and the loaddeflection curves start to deviate at larger deflections.…”
Section: Grain-size Effectcontrasting
confidence: 46%
“…This is called 'modelling of models'. This technique has been used before for laterally loaded piles (Barton, 1985;Nunez et al, 1988;Remaud, 1999;Terashi, 1989) to investigate solely the grain-size effect. Garnier et al (2007) developed a scaling catalogue for 'TC2 -physical modelling in geotechnics' and noted that no grain-size effect was detected in 'modelling of models' if the ratio between pile diameter and average grain size was larger than 45 (Nunez Table 2.…”
Section: Scaling In the Centrifugementioning
confidence: 99%
See 3 more Smart Citations